Different therapeutic responses to osimertinib as first-line treatment for cavitated and non-cavitated squamous cell lung cancer with rare EGFR exon 19 deletion: two case reports and a literature review - Ren, Jing; Cheng, Liang Xiao; Zhang, Rui; Zou, Zhi; Zhou, Yongzhao; Zheng, Xi (Frontiers in Oncology, 2025)
BackgroundCavitation is a special radiological feature of lung cancer, commonly observed in squamous cell lung cancer (SqCLC). This study intended to report two cases of cavitated and non-cavitated SqCLCs treated with epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) and discuss their different therapeutic responses.Case presentationTwo SqCLC patients with EGFR exon 19 deletions were treated with osimertinib as first-line therapy. One patient presented with a thick-walled cavitated lesion, while the other had a non-cavitated mass. After 3 months of osimertinib treatment, the cavitated SqCLC case showed disease progression. This patient subsequently underwent surgical resection of the primary tumor, followed by chemotherapy and immunotherapy, achieving an overall survival of 41 months to date. In contrast, the non-cavitated SqCLC case responded better to osimertinib, achieving partial remission with a progression-free survival of 14 months. Upon subsequent growth in both the primary lesion and lymph nodes, this patient began treatment with chemotherapy combined with immunotherapy, with a current overall survival of 31 months.ConclusionsThese cases suggest that osimertinib may be less effective as a first-line treatment for EGFR driver gene positive cavitated SqCLC than non-cavitated cases. Further research is needed to evaluate whether combining EGFR-TKIs with other therapies provides greater benefits than EGFR-TKIs alone for EGFR-positive cavitated SqCLC.